EVALUATING DUAL-IMPACT RISK MITIGATION STRATEGIES FOR ENHANCING SAFETY AND ENVIRONMENTAL SUSTAINABILITY IN HIGH-RISK INDUSTRIES - NISHANT SUBHASH PHAD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
There is a growing expectation for high-risk industries to manage both occupational safety and environmental sustainability, yet empirical evidence on the effectiveness of such dual-impact mitigation strategies is still limited. This research, therefore, investigates the impact of integrated safety environmental approaches on risk reduction across high-risk industries using a systematic literature review, thematic analysis, and expert validation interviews. A total of 67 high-quality academic and regulatory sources were analyzed, supported by a standardized composite risk scoring system that compares pre- and post-integration outcomes. Results from this indicate that integrated risk management far surpasses the performance of conventional, silo-based approaches by driving risk reductions of up to 40–48% in each of the Oil & Gas, Chemical, and Nuclear industries under consideration. System-based and standards-driven strategies, like Safety Management Systems, real-time monitoring, and combined ISO 45001/14001 implementation, demonstrated the highest levels of safety-environmental alignment. Environmental monitoring was followed by emergency response planning, hazardous material controls, and pollution-reduction initiatives, all of which ranked among the most common practices within the industry. The critical enabling role of regulatory frameworks is also highlighted within this study, where compliance spurs additional risk reductions in excess of 50% in some industries. Overall, dual-impact strategies enhance operational safety, reduce environmental harm, and build organizational resilience. The study emphasizes that there should be integrated frameworks to support decision-making on a risk basis and for advancing sustainability in high-risk industries.